The Adhesiveness of the PVD Coatings on Heat Treated Structural Steels - Stjepan Golubić*; Ivica Kladarić; Ivan Samardžić; Suzana Jakovljević (Tehnički Vjesnik, 2021)
PVD coatings on hard materials reduce adhesion and abrasion wear, while some types of coatings also reduce friction. The temperature of the PVD process is lower than the tempering temperature of steels, so there is no deformed parts and no input of new stresses. During the heat treatment, the PVD process is performed at the end because the PVD coating does not require any subsequent heat treatment. This paper investigates the effect of applying PVD coatings (cVIc and nACVIc) on adhesiveness to three quenched and tempered structural steels (45S20, C45E and 42CrMo4). Prior to coating, all steels were heat-treated within the process of normalization, quenching and tempering, and were treated to four different surface roughnesses. Results obtained by measuring adhesiveness are statistically analyzed. Based on the experimental tests, it is determined that the adhesiveness of applied PVD coatings to quenched and tempered steels depends more on the type of coating and on previous heat treatment of the steel, and less on the type of steel and initial roughness.